Incomplete immunization and its determinants among children in Africa: Systematic review and meta-analysis - Natnael Atnafu Gebeyehu; Kelemu Abebe Gelaw; Getachew Asmare Adella; Kirubel Dagnaw Tegegne; Biruk Adie Admass; Molalegn Mesele Gesese (Taylor & Francis Group, 2023)
Immunization is one of the most cost-effective measures to prevent morbidity and mortality in children. Therefore, the purpose of this systematic review and meta-analysis was to determine the pooled prevalence of incomplete immunization among children in Africa as well as its determinants. PubMed, Google Scholar, Scopus, Science Direct, and online institutional repository homes were searched. Studies published within English language, with full text available for searching, and studies conducted in Africa were included in this meta-analysis. A pooled prevalence, Sub-group analysis, sensitivity analysis and meta-regression were conducted. Out of 1305 studies assessed, 26 met our criteria and were included in this study. The pooled prevalence of incomplete immunization was 35.5% (95% CI: 24.4, 42.7), I2 = 92.1%). Home birth (AOR=2.7; 95% CI: 1.5-4.9), rural residence (AOR = 4.6; 95% CI: 1.1-20.1), lack of antenatal care visit (AOR = 2.6; 95% CI: 1.4-5.1), lack of knowledge of immunizations (AOR=2.4; 95% CI: 1.3-4.6), and maternal illiteracy (AOR = 1.7: 95%CI: 1.3-2.0) were associated with incomplete immunization. In Africa, the prevalence of incomplete immunization is high. It is important to promote urban residency, knowledge of immunization and antenatal follow up care.